Pengaruh Flexible Working Hours (FWH), Employer Branding dan Media Sosial Terhadap Minat Melamar Kerja Generasi Zoomer - Zulfirhan Maulana; Henri Dwi Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of Flexible Working Hours (FWH), Employer Branding (EB), and Social Media (SM) on Job Application Interest (JAI) among Generation Zoomer in Surakarta. Using a quantitative explanatory approach, the research involved 121 respondents selected through non-probability purposive sampling. Data were collected via online questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS software. The results show that FWH has the most significant effect on job application interest, followed by the effects of Employer Branding and Social Media, although their contributions are smaller. The model explains most of the variability in job application interest, indicating that these factors have strong relevance in predicting the interest of Generation Zoomer in applying for jobs. This study provides valuable insights for companies in designing policies that attract potential employees, particularly Generation Zoomer.